Hypercyclic operators on algebra of symmetric analytic functions on _p - Mozhyrovska, Z.G. (Carpathian Mathematical Publications, 2016)
In the paper, it is proposed a method of construction of hypercyclic composition operators on H(C^n) using polynomial automorphisms of C^n and symmetric analytic functions on _p. In particular, we show that an "symmetric translation" operator is hypercyclic on a Frechet algebra of symmetric entire functions on _p which are bounded on bounded subsets.